An investigation of the effect of racism in the Uniting Presbyterian Church in Southern Africa : an ethical-theological case study of the Amathole Presbytery - Veldsman, Daniel Petrus (University of Pretoria, 2024)
Dissertation (MTh (Systematic and Historical Theology))--University of Pretoria, 2023.